Cost and Production Duality: The Case of the Regulated Firm - OUELLETTE, PIERRE; VIGEANT, STÉPHANE (Journal of productivity analysis, 2001)
This paper examines a generalization of cost-production duality for regulated firms. It derives an equivalency between the production function and conditional factor demands for the case where the firm's optimization problem is subject to a set of additional (regulatory) constraints. This procedure is extended to an optimization problem within a dynamic framework which leads to the recovery of the firm's technology.